PENGARUH PENGERINGAN TERHADAP DAYA HIDUP DAN INTENSITAS SERANGAN BUBUK KAYU KERING HETEROBOSTRYCHUS AEQUALIS WAT PADA KAYU PULAI (ALSTONIA SCHOLARIS R.Br) - Ginuk Sumarni; Jasni Jasni (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
Heterobostrychus aequalis Wat is very important wood destroying insect other than termites. In this experiment pulai wood samples (Alstonia scholaris R.Br) taken from above and under a girdle of cut around tree stem were dried at temperature 40˚C, 60˚C, 90°C, 100°c, 120°c, 150°C, 200°c and air temperature. On each side of the samples of 1,5 cm x 5 cm x 7 cm. Into in dimension ten holes were made the hole larvaes of 1,5 month old were placed. The observations were made after six week period.Wood dried at temperature 40°C had the lowest starch content i.e 13,40 % for wood samples the girdle and 11,15 % for wood samples under the girdle, white the intensity of insect's attack can be rated os moderate (with score 67,25 and 65,75).